2022
DOI: 10.3390/ijms232214017
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification, Characterization, and Transcriptomic Analysis of the Cyclin Gene Family in Brassica rapa

Abstract: Cyclins are involved in cell division and proliferation by activating enzymes required for the cell cycle progression. Our genome-wide analysis identified 76 cyclin genes in Brassica rapa, which were divided into nine different types (A-, B-, C-, D-, H-, L-, P-, T-, and SDS-type). Cyclin genes were unevenly scattered on all chromosomes, with a maximum of 10 on A08 and a minimum of 2 on A04. The gene structure and conserved motif analysis showed that the cyclins which belonged to the same type or subgroup have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Moreover, the insertion of exogenous sequences into the VIGS vector may limit the fitness of the recombinant virus, which can result in genomic deletions after a few replicative cycles. Despite these potential limitations, it is expected that the VIGS technique will increase its scope in the cannabis system by exploiting the ability of VIGS-mediated down expression to be inherited by the infected plant progeny through RNA-directed DNA methylation (RdDM) [62]. RdDM experiments are still in their very early days but may represent a future tool for the genetic improvement of cannabis through stable epigenetic modifications.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the insertion of exogenous sequences into the VIGS vector may limit the fitness of the recombinant virus, which can result in genomic deletions after a few replicative cycles. Despite these potential limitations, it is expected that the VIGS technique will increase its scope in the cannabis system by exploiting the ability of VIGS-mediated down expression to be inherited by the infected plant progeny through RNA-directed DNA methylation (RdDM) [62]. RdDM experiments are still in their very early days but may represent a future tool for the genetic improvement of cannabis through stable epigenetic modifications.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a large amount of plant growth and development associated genes lost their functional domains, which were caused by these three types of events regulation. Cyclin domains were considered as core elements of cyclin families and played crucial roles in controlling the cell progression via activating cyclin-dependent kinase enzymes [ 33 ]. Five out of six non-domain isoforms showed much higher concentrations in rhizome than others, indicating that AS event might exert a certain extent of negative influence on rhizome growth.…”
Section: Discussionmentioning
confidence: 99%
“…Plant RNA virus‐based vectors present a potential solution to these challenges. Historically, these vectors were used for virus‐induced gene silencing (VIGS), which exploits antiviral gene silencing to rapidly phenotype gene knockdowns without the need to generate transgenic plants (Zulfiqar et al ., 2023: Rössner et al ., 2022). Recent work has demonstrated that RNA viruses can also be used to deliver genetic cargos to somatic tissues across a range of plants (Torti et al ., 2021).…”
Section: Overcoming Transgenesis Bottlenecks Via Somatic Gene Deliverymentioning
confidence: 99%